Alu element-containing RNAs maintain nucleolar structure and function - Caudron-Herger, Maïwen; Pankert, Teresa; Seiler, Jeanette; Németh, Attila; Voit, Renate; Grummt, Ingrid; Rippe, Karsten (The EMBO journal, 2015)
Abstract Non-coding RNAs play a key role in organizing the nucleus into functional subcompartments. By combining fluorescence microscopy and RNA deep-sequencing-based analysis, we found that RNA polymerase II transcripts originating from intronic Alu elements (aluRNAs) were enriched in the nucleolus. Antisense-oligo-mediated depletion of aluRNAs or drug-induced inhibition of RNA polymerase II activity disrupted nucleolar structure and impaired RNA polymerase I-dependent transcription of rRNA genes. In contrast, overexpression of a prototypic aluRNA sequence increased both nucleolus size and levels of pre-rRNA, suggesting a functional link between aluRNA, nucleolus integrity and pre-rRNA synthesis. Furthermore, we show that aluRNAs interact with nucleolin and target ectopic genomic loci to the nucleolus. Our study suggests an aluRNA-based mechanism that links RNA polymerase I and II activities and modulates nucleolar structure and rRNA production.